Splitting of Low-Rank ACM Bundles on Hypersurfaces of High Dimension. Issue 3 (3rd March 2016) - Tripathi, Amit
Abstract : Let X be a smooth projective hypersurface. We derive a splitting criterion for arithmetically Cohen–Macaulay bundles over X . As an application, we show that any rank 3 ACM vector bundle over X splits when dim  X  ≥ 7. We also derive a splitting result for rank 4 arithmetically Cohen–Macaulay bundles.